Assessing Changes in Intercultural Sensitivity among Agricultural Students Exposed to International Experiences - Maria Fabregas Janeiro; Kathleen D. Kelsey; J. Shane Robinson (Journal of International Agricultural and Extension Education, 2011)
The purpose of this study was to assess changes in intercultural sensitivity among Agriculture college students at a land-grant university who participated in a designated international I-course or a faculty-led short study abroad program to America, Asia/Oceania, and Europe. Using the Intercultural Development Inventory (IDI).A nonequivalent group design pretest, posttest, with a comparison group, was used for data collection and analysis. One hundred and sixty-two students, clustered into five groups, participated in the study. The data were analyzed using split-plot factorial design 5 x 2. Findings indicated that all five groups were in the Ethnocentric Phase of the developmental continuum for both the pre and posttest, among the groups regarding development of intercultural sensitivity as a result of an international experience or I-course. The authors recommend that course facilitators include facets of intercultural dimensions in the curriculum as a means for assisting students acquire intercultural competence. Interventions should be designed according to individual levels of intercultural sensitivity. Reflexive journaling and group discussions should be used as an integral partof institutional curricular enhancement plans to increase intercultural competence. Institutional, intercultural goals should include moving students toward the acceptance stage of the Developmental Model of Intercultural Sensitivity (DMIS). Further research should identify specific variables related to developing intercultural sensitivity among college students.
Keywords: Intercultural Sensitivity; higher education; curriculum development; student development; competencies; program evaluation; professional development